Impact of the human papillomavirus status on the development of high‐grade cervical intraepithelial neoplasia in women negative for intraepithelial lesions or malignancy at the baseline: A 9‐year Swedish nested case‐control follow‐up study. Issue 2 (10th December 2018) - Fröberg, Maria; Östensson, Ellinor; Belkić, Karen; Oštrbenk, Anja; Poljak, Mario; Mints, Miriam; Arbyn, Marc; Andersson, Sonia
Abstract : Background: The causal relation between high‐risk human papillomavirus (HPV) and cervical cancer and its precursor lesions has led to the use of sensitive HPV molecular tests for screening. This study examined the impact of the baseline HPV status on the future risk of cervical intraepithelial neoplasia grade 2 or worse (CIN2+) among women with cytology negative for intraepithelial lesions or malignancy (NILM). Methods: This was a nested case‐control study including women with NILM baseline cytology participating in the Swedish cervical screening program in 2005‐2007. Ninety‐six cases of CIN2+ and 5 age‐matched controls per case were identified through the National Cervical Screening Registry by follow‐up through 2014. Baseline liquid‐based cytology samples were tested for HPV. Conditional logistic regression analysis was used to calculate odds ratios (ORs) with confidence intervals (CIs). Results: The risk of future high‐grade cervical intraepithelial neoplasia (CIN) was strongly associated with the baseline HPV status. For women younger than 30 years, HPV‐16/18 showed a significant association with future risk for CIN2+ (OR, 9.44; 95% CI, 3.37‐26.4). Other HPV types were not significantly associated with future CIN2+ in these younger women. For women 30 years old or older, both HPV‐16/18 and other HPV subtypes conferred a significant risk. Conclusions: The presence of HPV‐16/18 among women with NILM cytology is associated with an elevated future risk of high‐grade CIN. HPV types other than HPV‐16/18 seem to have a greater impact on women 30 years old or older than younger women. Women with NILM cytology and HPV‐16/18 need specific follow‐up management within screening. Abstract : Women with cervical cytology negative for intraepithelial lesions or malignancy who are infected with high‐risk human papillomavirus are at future risk for high‐grade cervical intraepithelial neoplasia. Infection with human papillomavirus subtype 16 or 18 is the most powerful risk predictor, especially for younger women negative for intraepithelial lesions or malignancy.